STUDI KELAYAKAN INTERNAL, EKSTERNAL, DAN KESESUAIAN LAHAN DALAM PERSPEKTIF EKONOMI LINGKUNGAN - Diny Amelia Amelia; Rosalina Kumalati; Ellyn Normelani (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2025)
Land feasibility studies play a crucial role in ensuring the sustainable utilization of natural resources from both economic and environmental perspectives. This study aims to analyze internal feasibility, external feasibility, and land suitability within the framework of environmental economics. The method employed is a literature review, focusing on previous studies related to land evaluation, economic feasibility, and the environmental impacts of land use. The findings indicate that internal feasibility emphasizes efficiency in land utilization and long-term economic benefits, while external feasibility highlights social, regulatory, and ecological aspects. Meanwhile, land suitability analysis demonstrates the importance of aligning biophysical conditions with planned land use to minimize degradation and optimize productivity. Integrating these three aspects provides a comprehensive framework for sustainable development that balances economic value with environmental quality and community welfare. In conclusion, internal and external feasibility assessments, combined with land suitability analysis, serve as strategic instruments for guiding environmentally sound planning and policy-making.